Noteworthy record of melanism in Leopardus tigrinus from El Cocuy National Natural Park, Colombia - Cáceres-Martínez, Carlos H.; Zamora-Abrego, Joan Gastón; González-Maya, José F. (Therya Notes, 2023)
Melanism is the excess of dark pigmentation that partially or completely covers the body of an animal. The presence of melanic individuals is relatively common in several feline species. The objective of this note is to report the second case of melanism in free-living Leopardus tigrinus in Colombia. For the country, there is only one published record for the Department of Caldas. Between June 2012 and March 2020, 158 single camera-trap stations were set up in 5 protected areas in the Eastern Cordillera of Colombia. After almost 8 years of monitoring and with a sampling effort of 60,704 nights/trap, we recorded one melanic individual of L. tigrinus, in El Cocuy National Natural Park. So far the presence of melanic individuals of L. tigrinus has been recorded mainly in Brazil (although once its taxonomy is clarified it may correspond to a different species). For Colombia, there is one documented record more than 350 km away from ours (Department of Boyacá). It is considered that this phenomenon may be an adaptive response of the species to environmental evolutionary pressures and has been proposed as a niche segregation strategy; however, given the rarity of this phenotype in the study area, and in general throughout its distribution, it is necessary to gather more evidence that could potentially explain the selective forces that favor or limit this type of phenotypic expression.